Skill-related performance in soccer: a systematic review - Aquino, R.; Puggina, E. F.; Alves, I. S.; Garganta, J. (Human Movement, 2016)
The aim of the study was to evaluate and organize systematically the available literature on skill-related performance in young and adult male soccer players in an attempt to identify the most common topics, ascertain the weaknesses, and elucidate the main contributions of the scientific papers on this issue. A systematic review of the Institute for Scientific Information (ISI) Web of Knowledge database was performed in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) guidelines. The keywords `football` and `soccer` were used, each associated with the following terms: `technical analysis,` `technical performance,` `technical activity,` `technical skill,` `technical demands,` `technical profiles,` `technical characteristics,` `technical actions,` `technical scores,` `technical ability,` `motor skills,` and `skill acquisition`. From the 2830 papers, only 60 were reviewed, of which 75% had been published in years 2011-2015 and 53.3% concerned professional or seniors players (above the U-20 category). Out of the 41 papers that analysed the skill-related performance in the match, 48.8% evaluated the performance in small-sided and conditioned games. Among the 27 papers that used validated instruments, 88.9% assessed technical actions outside the match context (e.g. dribbling, shooting tests). Future research should pay attention to the definition and classification of the skill-related variables under investigation in match context and propose tests for measured skill-related performance in soccer, considering that the representativeness task design allies the players` possibilities of action to the situation of the match.